A corpus-based analysis of perception-related vocabulary in English and Uzbek (Texas Journal of Philology, Culture and History, 2025)
This article explores the lexical and semantic features of perception-related vocabulary in English and Uzbek through a corpus-based approach. Previous research has highlighted the significance of perception verbs and adjectives for understanding cross-linguistic conceptualization of sensory experiences (Biber, Conrad, & Reppen, 1998; Nazarova, 2018). Quantitative and qualitative analyses reveal convergences and divergences in frequency, collocational patterns, semantic extension, and grammatical behavior of perception words (such as see, hear, feel, taste, smell in English; ko‘rmoq (to see), eshitmoq (to hear), sezmoq (to feel), tatib ko‘rmoq (to taste), hidlamoq (to smell) in Uzbek). While direct perceptual verbs exhibit high frequency across both languages, notable differences appear in their metaphorical extensions. The results illuminate how cultural and linguistic structures mediate perception words, yielding implications for translation, language teaching, and lexicography